KN

Cho x = √(2+√(2+√3))-√(6-3√(2+√3))

Tính S = x4-16x2

Giúp mik ik mik tik cho

H24
20 tháng 8 2020 lúc 22:14

Ta có :\(x^2=2+\sqrt{2+\sqrt{3}}+6-3\sqrt{2+\sqrt{3}}-2\sqrt{\left(2+\sqrt{2+\sqrt{3}}\right)\left(6-3\sqrt{2+\sqrt{3}}\right)}\)

              \(=8-2\sqrt{2+\sqrt{3}}-2\sqrt{3\left(2+\sqrt{2+\sqrt{3}}\right)\left(2-\sqrt{2+\sqrt{3}}\right)}\)

              \(=8-\frac{2}{\sqrt{2}}\sqrt{4+2\sqrt{3}}-2\sqrt{3\left(2^2-\sqrt{2+\sqrt{3}}^2\right)}\)       

              \(=8-\sqrt{2}\sqrt{\sqrt{3}^2+2\cdot1\sqrt{3}+1^2}-2\sqrt{3\left(4-2-\sqrt{3}\right)}\)

              \(=8-\sqrt{2}\sqrt{\left(\sqrt{3}+1\right)^2}-2\sqrt{3}\sqrt{2-\sqrt{3}}\)

               \(=8-\sqrt{2}\left(\sqrt{3}+1\right)-\frac{2\sqrt{3}}{\sqrt{2}}\sqrt{4-2\sqrt{3}}\)

               \(=8-\left(\sqrt{6}+\sqrt{2}\right)-\sqrt{6}\sqrt{\left(\sqrt{3}-1\right)^2}\)

               \(=8-\sqrt{6}-\sqrt{2}-\sqrt{6}\left(\sqrt{3}-1\right)\)

               \(=8-\sqrt{6}-\sqrt{2}-\sqrt{18}+\sqrt{6}\)

               \(=8-\sqrt{2}-\sqrt{18}\)

               \(=8-\sqrt{2}\left(3+1\right)=8-4\sqrt{2}\)

\(\Rightarrow x^4-16x^2=\left(8-4\sqrt{2}\right)^2-16\left(8-4\sqrt{2}\right)\)

                          \(=8^2+4^2\cdot\sqrt{2}^2-2\cdot8\cdot4\sqrt{2}-16\cdot8+16\cdot4\sqrt{2}\)

                          \(=64+32-64\sqrt{2}-128+64\sqrt{2}\)

                          \(=-32\)

         Vậy \(x^4-16x^2=-32\)

Tại hạ làm bừa có gì mong đạo hữu lượng thứ =))

Bình luận (0)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
CT
Xem chi tiết
NQ
Xem chi tiết
HT
Xem chi tiết
AD
Xem chi tiết
PT
Xem chi tiết
NB
Xem chi tiết
NQ
Xem chi tiết
ND
Xem chi tiết
LT
Xem chi tiết